2018
DOI: 10.1177/0030727018794973
|View full text |Cite
|
Sign up to set email alerts
|

Land suitability levels for rainfed maize under current conditions and climate change projections in Mexico

Abstract: An assessment of land suitability classes for rainfed maize (spring–summer agricultural cycle) with current climate conditions (1950–2000) and projected climate change scenarios was carried out for Mexico. The method considered the most restrictive factors or agroclimatic requirements from different variables needed by rainfed maize. These factors were analyzed spatially in a geographic information systems (GIS) context, resulting in areas classified into four suitability levels: high, medium, low, and not sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…For example, Ojara et al (2021) projected that area highly suitable for maize in Eastern Africa will decrease by more than 50% under the RCP8.5 scenario by the mid-century but if extreme indices were included, the decreases could be worse. Many studies have projected maize suitability changes without incorporating extreme variables (Holzkämper et al, 2013;Adisa et al, 2018;Lopez-Blanco et al, 2018;Kogo et al, 2019;Mumo et al, 2021;Yang et al, 2021), and the reported changes may need to be revisited in light of our findings.…”
Section: Discussionmentioning
confidence: 91%
“…For example, Ojara et al (2021) projected that area highly suitable for maize in Eastern Africa will decrease by more than 50% under the RCP8.5 scenario by the mid-century but if extreme indices were included, the decreases could be worse. Many studies have projected maize suitability changes without incorporating extreme variables (Holzkämper et al, 2013;Adisa et al, 2018;Lopez-Blanco et al, 2018;Kogo et al, 2019;Mumo et al, 2021;Yang et al, 2021), and the reported changes may need to be revisited in light of our findings.…”
Section: Discussionmentioning
confidence: 91%
“…To overcome the climatic challenges for the agricultural sector in the north of Mexico, farmers have implemented irrigation management to grow animal feed crops such as sorghum and wheat, leaving staple foods production to the southern and central Mexico (Eakin et al, 2014b). The south seems prone to be affected not only by climate change (Monterroso et al, 2011;López-Blanco et al, 2018;Murray-Tortarolo et al, 2018) but also by socioeconomic constraints. Southern states of Mexico, like Chiapas, have lagged in investment (Fox and Haight, 2010), and the adoption of mechanization is impossible due to topography restrictions (Eakin et al, 2014c).…”
Section: Discussionmentioning
confidence: 99%
“…Bagherzadeh and Gholizadeh [11] Artificial neural network (ANN) Bagherzadeh et al [12] Fuzzy approach Danvi et al [13] Machine learning (ML) Lopez-Blanco et al [14] Fuzzy-based method + ML Raza et al [15] Fuzzy-based method Bhermama et al [16] GIS+ land suitability evaluation (LSE)…”
Section: Authors Methods Employed For Analysismentioning
confidence: 99%